2002
DOI: 10.1074/jbc.m106813200
|View full text |Cite
|
Sign up to set email alerts
|

'Srcasm: a Novel SrcActivating and SignalingMolecule

Abstract: The Src family tyrosine kinase, Fyn, can facilitate regulation of cell proliferation and differentiation. Mice with mutations in the fyn gene have defects in the brain, immune system, and epidermal differentiation. To identify molecules that may interact with Fyn in the epidermis, we performed a yeast two-hybrid interaction screen of a murine keratinocyte library. A novel adaptor-like molecule was isolated and termed Srcasm for Src activating and signaling molecule. Murine Srcasm is a 52.7-kDa protein that con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(87 citation statements)
references
References 66 publications
1
85
1
Order By: Relevance
“…By the yeast twohybrid interaction screen of a murine keratinocyte library, Seykora et al (26) found that TOM1L1 interacts with Fyn. In the murine brain, the distribution of TOM1L1 mRNA is correlated with that of Fyn, and the result of co-transfecting Fyn and TOM1L1 suggests that Fyn phosphorylates TOM1L1 (26). Recently, it was observed that EGF receptor stimulation induces the tyrosine phosphorylation of TOM1L1 in keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
“…By the yeast twohybrid interaction screen of a murine keratinocyte library, Seykora et al (26) found that TOM1L1 interacts with Fyn. In the murine brain, the distribution of TOM1L1 mRNA is correlated with that of Fyn, and the result of co-transfecting Fyn and TOM1L1 suggests that Fyn phosphorylates TOM1L1 (26). Recently, it was observed that EGF receptor stimulation induces the tyrosine phosphorylation of TOM1L1 in keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Src-activating and signaling molecule (Srcasm) is a substrate and negative regulator of SFKs (66,67). Srcasm has been shown to limit keratinocyte proliferation, promote differentiation, and negatively regulate EGFR and SFK signaling in primary human keratinocytes (68,69).…”
Section: Pathophysiologic Features Of Csccs Ras Family Members Of Prmentioning
confidence: 99%
“…Localization of Fyn on Endosomes after EGF Internalization-It has been described previously that Srcasm (Src activating and signaling molecule), the mouse homolog of Tom1L1, is capable of interacting with Fyn, Grb2, and the regulatory subunit of phosphoinositide 3-kinase, p85, in a phosphorylationdependent manner through several SH2 and SH3 domains located in the C-terminal portion of Srcasm (40). The motifs responsible for these interactions are conserved between mouse and human, indicating that Tom1L1 is probably also able to bind the same proteins.…”
Section: Tom1l1mentioning
confidence: 99%
“…In the present work, we characterize the interaction of Tom1L1 with TSG101 and Hrs, as well as the recruitment of Tom1L1 to endosomes after Hrs or active Fyn overexpression. We feel the presence of motifs in the Tom1L1 C-terminal region that mediates interactions with signaling proteins, such as the tyrosine kinase Fyn and Grb-2, and the regulatory subunit of phosphoinositide 3-kinase, p85 (40), makes this protein an excellent candidate to connect signaling and degradative pathways.…”
mentioning
confidence: 99%